Copper and cobalt deficiencies in cattle and sheep in some regions of Brazil - Tokarnia, Carlos Hubinger; Guimarães, Jorge Almeida; Canella, Camillo F. C.; Döbereiner, Jürgen (Pesquisa Agropecuaria Brasileira, 2014)
The studies consisted in collecting the history of diseases possibly caused by mineral deficiencies, clinical observations and examinations of cattle and sheep, post-mortem examinations, histopathological studies, and in copper and cobalt determinations of liver samples. Copper deficiency was revealed in the coastal area of the Município de Campos in the northern part of the State of Rio de Janeiro, in the area in Santa Catarina located between the Serra do Mar and the Atlantic Ocean, in the Município de Jaciara, State of Mato Grosso, in the "agreste" of the State of Piauí and in the forest area of the Município de Macapá, Territory of Amapá. Cobalt deficiency was revealed in northern Espírito Santo and in the forest area of the Município de Macapá, Territory of Amapá.